UPAYA MENINGKATKAN PARTISIPASI MASYARAKAT DALAM TANGGAP BENCANA DI DUSUN NDUNGGA DESA NDUNGGA KECAMATAN ENDE TIMUR KABUPATEN ENDE TAHUN 2017 - Aris Wawomeo (Kelimutu Nursing Journal, 2022)
Disaster is an event or series of events that threaten and disrupt people's lives and livelihoods caused by both natural and / or non-natural factors and human factors resulting in the occurrence of human casualties, environmental damage, property loss and psychological impact. Disaster is only possible there is a very high vulnerability factor available in the community. One of the factors of vulnerability in the community is low knowledge related to disaster. The purpose of community service activities is to increase community participation in disaster response. The targets of the activity are community members in Ndungga Hamlet, Ndungga Village, East Ende District. The activities using lecture and question and answer methods related to disaster materials with the media used are posters and leaflets. In addition, it uses a demonstration method of simple actions that communities can take in disaster situations. The results obtained, among others, the level of public participation is quite high. It is assessed based on several aspects: the community prepares all local tools and materials for the training, present on time, the attendees are 26 people or 88% of the targeted audience will be present are 30 people, eleven participants asked during the lecture and question and answer process, many who held up to answer the questions posed by the team and all questions answered correctly, re-demonstrate all the skills exhibited by the team, the expectation of the community for similar activities to be carried out again. Based on these results, it was concluded that community service activity to improve community ability in emergency response was successfully implemented. It is therefore recommended that similar activities should continue to be implemented in order for the community to be self-sufficient to cope with the disaster situation in the absence of any external relief efforts